Defensins from the tick Ixodes scapularis are effective against phytopathogenic fungi and the human bacterial pathogen Listeria grayi - Miray Tonk; Alejandro Cabezas-Cruz; James J Valdés; Ryan OM Rego; Tereza Chrudimská; Martin Strnad; Radek Šíma; Lesley Bell-Sakyi; Zdeněk Franta; Andreas Vilcinskas; Libor Grubhoffer; Mohammad Rahnamaeian (Parasites & Vectors, 2014)
Abstract Background Ixodes scapularis is the most common tick species in North America and a vector of important pathogens that cause diseases in humans and animals including Lyme disease, anaplasmosis and babesiosis. Tick defensins have been identified as a new source of antimicrobial agents with putative medical applications due to their wide-ranging antimicrobial activities. Two multigene families of defensins were previously reported in I. scapularis. The objective of the present study was to characterise the potential antimicrobial activity of two defensins from I. scapularis with emphasis on human pathogenic bacterial strains and important phytopathogenic fungi. Methods Scapularisin-3 and Scapularisin-6 mature peptides were chemically synthesised. In vitro antimicrobial assays were performed to test the activity of these two defensins against species of different bacterial genera including Gram-positive bacteria Staphylococcus aureus, Staphylococcus epidermidis, and Listeria spp. as well as Gram-negative bacteria Escherichia coli, Pseudomonas aeruginosa along with two plant-pathogenic fungi from the genus Fusarium. In addition, the tissue-specific expression patterns of Scapularisin-3 and Scapularisin-6 in I. scapularis midgut, salivary glands and embryo-derived cell lines were determined using PCR. Finally, tertiary structures of the two defensins were predicted and structural analyses were conducted. Results Scapularisin-6 efficiently killed L. grayi, and both Scapularisin-3 and Scapularisin-6 caused strong inhibition (IC50 value: ~1 μM) of the germination of plant-pathogenic fungi Fusarium culmorum and Fusarium graminearum. Scapularisin-6 gene expression was observed in I. scapularis salivary glands and midgut. However, Scapularisin-3 gene expression was only detected in the salivary glands. Transcripts from the two defensins were not found in the I. scapularis tick cell lines ISE6 and ISE18. Conclusion Our results have two main implications. Firstly, the anti-Listeria and antifungal activities of Scapularisin-3 and Scapularisin-6 suggest that these peptides may be useful for (i) treatment of antibiotic-resistant L. grayi in humans and (ii) plant protection. Secondly, the antimicrobial properties of the two defensins described in this study may pave the way for further studies regarding pathogen invasion and innate immunity in I. scapularis.